KLAUSULA BAKU DALAM PERJANJIAN ENDORSEMENT DIKAITKAN DENGAN ASAS KEBEBASAN BERKONTRAK - Alya Yudityastri; , Suraji (Jurnal Privat Law, 2020)
AbstractThis article aims to find out the validity of standard agreements in general and specially on endorsement  agreement. Validity of the endorsement agreement is reviewed from the Civil Code, Law Number 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, Law Number 8 of 1999 concerning Consumer Protection. In addition to knowing the suitability of the endorsement agreement that contains a standard contract clause with the principle of freedom of contract. Legal writing in this study uses research normative law with the statutory approach and conceptual approach. Research result it is known that the endorsement agreement is an example of a standard agreement with through the electronic system is in accordance with the provisions of the validity of the agreement according to the Civil Code, Law Number 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, Law Number 8 of 1999 concerning Protection Consumer. Standard agreement if it is related to the principle of freedom of contract is still being the debate over the suitability. Some are of the view that standard agreements are included in the terms of the endorsement agreement, are not in accordance with the principle of freedom of contract because of intermediaries the parties do not have a balanced bargaining position. Others argue that the agreement is in accordance with the principle of freedom of contract provided there is no clause exoneration in it.Keywords: Endorsement; Endorsement Contract; Standard Contract Clauses; Principle of Contract Freedom AbstrakArtikel ini bertujuan untuk mengetahui keabsahan perjanjian baku secara umum dan khususnya pada  perjanjian endorsement. Keabsahan perjanjian endorsement ditinjau dari KUHPerdata, Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik, Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Selain itu untuk mengetahui kesesuaian perjanjian endorsement yang memuat klausula kontrak baku dengan asas kebebasan berkontrak. Penulisan hukum dalam penelitian ini menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian diketahui bahwa perjanjian endorsement yang merupakan salah satu contoh perjanjian baku dengan melalui sistem elektronik telah sesuai dengan ketentuan keabsahan perjanjian menurut KUHPerdata, Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik, Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Kesesuaian perjanjian baku dengan asas kebebasan berkontrak masih menjadi perdebatan. Beberapa berpandangan bahwa perjanjian baku termasuk di dalamnya perjanjian endorsement, tidak sesuai dengan asas kebebasan berkontrak karena di antara para pihaknya tidak memiliki posisi tawar yang seimbang. Sebagian lainnya berpendapat bahwa perjanjian tersebut telah sesuai dengan asas kebebasan berkontrak apabila tidak terdapat klausula eksonerasi di dalamnya.Kata Kunci: Endorsement; Perjanjian Endorsement; Perjanjian Baku; Asas Kebebasan Berkontrak;